PRIMARY NEUROENDOCRINE TUMOR OF THE ENDOMETRIUM, A RARE TUMOR: CASE SERIES - TIWARI, PRATEEK; PATIDAR, SHREENA; PAL, V. (International Journal of Current Pharmaceutical Research, 2025)
Objective: Endometrial NET is a rare disease with a poor prognosis. Due to its rarity, there are no evidence-based standards or international guidelines for the diagnosis and treatment of endometrial NETs. Methods: In this study, we present our experience with four cases of NETs of the endometrium to describe these rare tumors’ clinical characteristics and behaviour. The clinicopathological characteristics, treatment and prognosis, were analysed. Results: Most common age group for presentation was 50 to 70 y. Irregular vaginal bleeding was most common symptom at presentation. Three patients underwent surgery followed by adjuvant chemoradiation while one patient with metastatic disease underwent chemotherapy. Overall prognosis was poor with two patients died 12 mo and 24 mo, respectively. One patient was lost to follow-up after 39 mo and one patient was disease free till last follow-up. Conclusion: Given the aggressive nature of the disease, patients should be carefully observed and followed up regularly. More studies with a higher number of cases are required to establish a standard therapeutic protocol.